Bifurcation strategies using second-generation drug-eluting stents on clinical outcomes in diabetic patients - Cha, Jung-Joon; Hong, Soon Jun; Kim, Ju Hyeon; Lim, Subin; Joo, Hyung Joon; Park, Jae Hyoung; Yu, Cheol Woong; Kang, Jeehoon; Kim, Hyo-Soo; Gwon, Hyeon-Cheol; Chun, Woo Jung; Hur, Seung-Ho; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Diabetes mellitus (DM) is a critical risk factor for the pathogenesis and progression of coronary artery disease, with a higher prevalence of complex coronary artery disease, including bifurcation lesions. This study aimed to elucidate the optimal stenting strategy for coronary bifurcation lesions in patients with DM. Methods: A total of 905 patients with DM and bifurcation lesions treated with second-generation drug-eluting stents (DES) from a multicenter retrospective patient cohort were analyzed. The primary outcome was the 5-year incidence of target lesion failure (TLF), which was defined as a composite of cardiac death, target vessel myocardial infarction, and target lesion revascularization. Results: Among all patients with DM with significant bifurcation lesions, 729 (80.6%) and 176 (19.4%) were treated with one- and two-stent strategies, respectively. TLF incidence differed according to the stenting strategy during the mean follow-up of 42 ± 20 months. Among the stent strategies, T- and V-stents were associated with a higher TLF incidence than one-stent strategy (24.0% vs. 7.3%, p<0.001), whereas no difference was observed in TLF between the one-stent strategy and crush or culotte technique (7.3% vs. 5.9%, p=0.645). The T- or V-stent technique was an independent predictor of TLF in multivariate analysis (hazard ratio, 3.592; 95% confidence interval, 2.117–6.095; p<0.001). Chronic kidney disease, reduced left ventricular ejection fraction, and left main bifurcation were independent predictors of TLF in patients with DM. Conclusions: T- or V-stenting in patients with DM resulted in increased cardiovascular events after second-generation DES implantation.